DEVELOPMENT COLLABORATION INTER-LIBRARY COLLECTION IN UNIVERSITY - Veni Fitra Meilisa (Central Library of Universitas Sebelas Maret, 2019)
This paper attempts to describe descriptively about the Collaboration Development between Inter-Library Collections in Higher Education, the benefits and obstacles that occur. The method used is a literature review method in which this method contains references related to the discussion contained in this scientific work, in order to obtain theoretical information sourced from reading material such as books, national journals or other internal sources that can support the writing of works. this scientific. The purpose of this scientific work is to know descriptively about the process of collaboration in the development of collections between college libraries, then the benefits obtained as well as the obstacles that might occur and of course will be reading material for writers and readers. The conclusion in this paper is that the diversity of information needs and the limitation of human resources make none of the information provider institutions including libraries that are able to meet all of the information needs of their users. then the abundance of data and information in the current era makes the library a center for information services to provide the widest possible access to information to the public. this requires that libraries that act as information providers for both the academic community and outside, need collaboration between libraries. The cooperation that can be carried out includes cooperation in procurement, management, storage and lending between libraries. As we are united, we are firm, our divorce collapses. This means that there are responsibilities that are shared together and there are benefits that will be shared together.